Patient Outcomes and Service Delivery Differences in Physiotherapy Care: A Systematic Review Comparing Hospital-Based and Private Practice Models - Mohamad Reza Hilmy; Alika Shameela; Erlina Puspitaloka Mahadewi (Majapahit Journal of Islamic Finance and Management, 2026)
Physiotherapy services are an essential part of contemporary health care systems and are usually provided in hospitals or private practices. Variations in structure of organizations, service delivery systems, and clinical context among various models may impact patient outcomes and the quality of care. The objective of this study was to investigate the disparities in patient outcomes and the characteristics of physiotherapy service delivery across hospital-based and individual practice models via a systematic literature review. The review adhered to PRISMA criteria and examined peer-reviewed literature published from 2020 to 2025. A technique called thematic analysis was used to combine 27 studies that met the inclusion criteria. The results show that physiotherapy in hospitals is especially good at helping patients with complicated medical conditions, needs after surgery, and needs for care from several disciplines through controlled interventions and standard procedures. On the other hand, private practice physiotherapy has advantages in terms of service flexibility, accessibility, consistency of treatments, and higher patient satisfaction, particularly when it comes to treating chronic musculoskeletal diseases and outpatient populations. These findings indicate that hospital-based alongside private practice treatment models fulfill complementary functions within healthcare systems. Strategic insertion of both of these approaches may improve patient outcomes, make services more efficient, and encourage physiotherapy care that is more focused on the patient.